MASS MEDIA AND TERRORISM: DECONSTRUCTING THE RELATIONSHIP - Prayudi Prayudi (Jurnal Ilmu Komunikasi, 2008)
Issue of terrorism came to surface in this early twenty first century through a number of acts violence that have killed hundreds and injured thousands of people. At the same time, these events have been dominated the mass media contents. Principally, mass media and issue of terrorism are inseparable. This paper examines the relationship between mass media and terror- ism. It is done through the deconstruction of the concept of terrorism and how terrorism is understood as a communicational process. Further, this paper examines how mass media relates to terrorism.